Complexities in Genetics of Psoriatic Arthritis - Rahmati, Sara (Curr Rheumatol Rep, 2020)
PURPOSE OF THE REVIEW: To provide a general overview and current challenges regarding the genetics of psoriatic disease. With the use of integrative medicine, multiple candidate loci identified to date in psoriatic disease will be annotated, summarized, and visualized. Recent studies reporting differences in genetic architecture between psoriatic arthritis and cutaneous-only psoriasis will be highlighted. RECENT FINDINGS: Focusing on functional pathways that connect previously identified genetic variants can increase our understanding of psoriatic diseases. The genetic architecture differs between psoriatic arthritis and cutaneous-only psoriasis with arthritis-specific signals in linkage disequilibrium independent of the published psoriasis signals. SUMMARY: Integrative medicine is helpful in understanding cellular mechanisms of psoriatic diseases. Careful selection of the psoriatic disease cohort has translated into mechanistic differences among psoriatic arthritis and cutaneous psoriasis. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s11926-020-0886-x) contains supplementary material, which is available to authorized users.